The skeletal organic matrix from Mediterranean coral Balanophyllia europaea influences calcium carbonate precipitation. - Stefano Goffredo; Patrizia Vergni; Michela Reggi; Erik Caroselli; Francesca Sparla; Oren Levy; Zvy Dubinsky; Giuseppe Falini (PLoS ONE)
Scleractinian coral skeletons are made mainly of calcium carbonate in the form of aragonite. The mineral deposition occurs in a biological confined environment, but it is still a theme of discussion to what extent the calcification occurs under biological or environmental control. Hence, the shape, size and organization of skeletal crystals from the cellular level through the colony architecture, were attributed to factors as diverse as mineral supersaturation levels and organic mediation of crystal growth. The skeleton contains an intra-skeletal organic matrix (OM) of which only the water soluble component was chemically and physically characterized. In this work that OM from the skeleton of the Balanophyllia europaea, a solitary scleractinian coral endemic to the Mediterranean Sea, is studied in vitro with the aim of understanding its role in the mineralization of calcium carbonate. Mineralization of calcium carbonate was conducted by overgrowth experiments on coral skeleton and in calcium chloride solutions containing different ratios of water soluble and/or insoluble OM and of magnesium ions. The precipitates were characterized by diffractometric, spectroscopic and microscopic techniques. The results showed that both soluble and insoluble OM components influence calcium carbonate precipitation and that the effect is enhanced by their co-presence. The role of magnesium ions is also affected by the presence of the OM components. Thus, in vitro, OM influences calcium carbonate crystal morphology, aggregation and polymorphism as a function of its composition and of the content of magnesium ions in the precipitation media. This research, although does not resolve the controversy between environmental or biological control on the deposition of calcium carbonate in corals, sheds a light on the role of OM, which appears mediated by the presence of magnesium ions.